GIS 3D모델을 통한 AHP-TOPSIS 알고리즘 기반 해체공법 자동 선정 - 주현철; 강인석; Hyun-Chul Joo; Leen-Seok Kang (한국건설관리학회 논문집, 26(3), 2025)
The selection of the most important demolition method in a dismantling project is determined by various conditions and environmental factors, but in most cases, the method is selected based on the experience and subjective judgment of the field engineers. In addition, the characteristics of demolition methods are qualitative, making it difficult to select a demolition method suitable for demolition work. Therefore, this study suggests a 3D model of the building to be demolished based on GIS information and automatically extracts information from the GIS 3D model to select the primary demolition method. Then, an AHP-TOPSIS based algorithm was used to select the optimal demolition method among the first selected demolition methods, and the reliability of the results was verified through consistency verification and sensitivity analysis. As a result of the verification, the consistency of the AHP weights was 0.00625, which can be judged to be highly consistent. The sensitivity analysis of TOPSIS demolition method selection showed that there is no change in the final demolition method selection result by changing 10%, 20%, and 30%, so it can be judged to be highly reliable. Through this study, the existing demolition method selection process can be shortened by applying the demolition method selection algorithm, and the use of basic information for fast and accurate demolition method selection for the increasing demand for demolition work can be used to objectively select demolition methods through algorithms rather than the subjective experience of practitioners. 해체 공사에서 가장 중요한 해체공법의 선정은 다양한 조건들과 환경적 요인들에 의해서 결정되지만, 대부분 실무자의 경험과 주관적 판단에 의해 공법이 선정되고 있다. 또한 해체공법의 특성이 정성적으로 나타나 있어 해체 공사에 적합한 해체공법을 선정하기 어려운 실정이다. 본 연구에서는 GIS 정보를 기반으로 해체 대상 건축물의 3D모델을 제작하고 자동으로 GIS 3D모델의 정보를 추출하여 1차 해체공법을 선정한다. 그리고 AHP-TOPSIS 기반 알고리즘을 통해 1차로 선정된 해체공법 중에서 최적의 해체공법을 선정하고 일관성 검증과 민감도 분석을 통해 결과의 신뢰성을 검증한다. 검증 결과 AHP 가중치의 일관성 0.43%로 나타나 매우 높은 일관성을 가지고 있다고 판단할 수 있다. TOPSIS 해체공법 선정의 민감도 분석 결과 10%, 20%, 30%를 변경하여 최종 해체공법 선정 결과에 변동이 없으므로 신뢰도가 높다고 판단할 수 있다. 본 연구를 통해 기존의 해체공법 선정 과정을 해체공법 선정 알고리즘 적용을 통해 단축할 수 있었다. 그리고 증가하는 해체 공사 수요에 빠르고 정확한 해체공법 선정을 위한 기초 정보의 사용과 실무자의 주관적 경험이 아닌 알고리즘을 통해 객관적으로 해체공법을 선정할 수 있을 것이다.